Information Activities of the Ukrainian Diaspora in the Czechoslovak Republic (1930-1931) - Sverdlyk, Zoriana; Klynina, Tetiana (Journal of History Culture and Art Research, 2020)
The article deals with the informational component of the attempt to unite Ukrainian emigration in Czechoslovakia in the period of collision of the old political concepts of the Ukrainian National Republic and the hetmanate with the young nationalist movement of the Organization of Ukrainian Nationalists. The purpose of the article is to find out the nature of information activities of the Ukrainian Diaspora in Czechoslovakia in the period of active attempts of its ideological and political consolidation on a democratic basis in the Union of Ukrainian Emigrant Organizations. An analysis of the content of the press body of this association – the Bulletin Vistnyk – will help to understand the reasons for the defeat of the integration project in the environment of Ukrainian emigration in Czechoslovakia. The chronological boundaries are due to the period of active publishing of the Union. The subject of the study is the Ukrainian diaspora in Czechoslovakia, and the subject matter is its informational activity within the framework of the mentioned edition. The main sources of this article include the materials of the Central State Archives of Foreign Ukrainians, documents of the Central State Archives of higher authorities and governments of Ukraine as well as the articles published in the Tryzub Weekly, Memorandum to the League of Nations. The research implements structural and problematic methods for its analysis. The results suggest that in the Bulletin Vistnyk, the Union of Ukrainian Emigrant Organizations tried to promote the idea of uniting different organizations around a certain goal – the fight for their own statehood.